IMAJI KESETARAAN DALAM BINGKAI NEGARA: REPRESENTASI TANGGUNG JAWAB PEREMPUAN PADA TEMA HARI IBU DI INDONESIA - Barkatun Nisa Alfia Alfia; Dadang Anshori (Adabiyyāt: Jurnal Bahasa dan Sastra, 2026)
The commemoration of Mother's Day in Indonesia is a poignant moment that holds rich historical and ideological significance. Over time, Mother's Day has evolved in its meaning within social and political contexts. The themes carried by the Kementerian Pemberdayaan Perempuan dan Perlindungan Anak Republik Indonesia (KPPPA) in commemorating Mother's Day reflect the dynamics of thinking about women and their roles in society. This study examines the portrayal of women's responsibilities in the official themes commemorating Mother's Day in Indonesia over the past two decades (2005–2024). Using descriptive-analytical qualitative methods and Sara Mills' critical feminist discourse analysis approach, this study examines how the state shapes the social construction of women's roles through the language used in these themes. Data were collected through the documentation of themes released by the KPPPA, supported by secondary sources. The results of the analysis show that although women are positioned as active subjects in social change, the state still controls the narrative about women's ideal roles. The language in these themes functions as an instrument of power that regulates the meaning of equality, presenting women's responsibilities ambivalently: between recognizing agency and reproducing normative ideological values.